2003
DOI: 10.1029/2002gc000309
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic processes under mid‐ocean ridges: A detailed mineralogic study of lavas from East Pacific Rise 9°30′N, 10°30′N, and 11°20′N

Abstract: [1] Detailed petrologic study has been made for lavas from the northern East Pacific Rise (EPR) 9°30 0 N has nonrobust magma supply and no shallow melt lens. Lavas from all three localities are sparsely phyric and glassy, containing plagioclase ± olivine ± pyroxene. Typically, the lavas contain several to many (up to seven) distinct chemical groups of plagioclase that are not always distinct texturally. The lavas may also contain up to three chemically distinct groups of olivine and two groups of pyroxene. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 116 publications
(172 reference statements)
1
14
0
Order By: Relevance
“…Data presented here are consistent with the Pan and Batiza [2003] model and strongly support complex crystal‐melt interactions between various melts and accumulating crystals in the lower crust and upper mantle. Such interactions have also been proposed based on mineralogic evidence in gabbroic sections formed at fast spreading centers (e.g., Hess Deep [ Natland and Dick , 1996]) and from some ophiolites, e.g., Oman [ Kelemen et al , 1997].…”
Section: Broader Implications For Ocean Crust Forming Processessupporting
confidence: 86%
See 2 more Smart Citations
“…Data presented here are consistent with the Pan and Batiza [2003] model and strongly support complex crystal‐melt interactions between various melts and accumulating crystals in the lower crust and upper mantle. Such interactions have also been proposed based on mineralogic evidence in gabbroic sections formed at fast spreading centers (e.g., Hess Deep [ Natland and Dick , 1996]) and from some ophiolites, e.g., Oman [ Kelemen et al , 1997].…”
Section: Broader Implications For Ocean Crust Forming Processessupporting
confidence: 86%
“…Primitive NMORB melts have molar Ca/Na ratios that are too low to crystallize anorthite under equilibrium or near‐equilibrium and this is illustrated by the absence of highly calcic plagioclase phenocrysts in NMORB lavas. Consequently, the common presence of anorthite‐bytownite xenocrysts in erupted NMORB lavas [ Sinton et al , 1993; Nielsen et al , 1995; Pan and Batiza , 2003] and anorthite‐bytownite cumulates in ophiolites is enigmatic. Similarly, the cumulate described here contains a significant amount of anorthite, particularly as a cumulate phase during the Stage 1 precipitation of plagioclase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be determined texturally (e.g., Dungan and Rhodes, 1978) and/or compositionally; most olivine and plagioclase crystals in MORB are more primitive than those in equilibrium with the host basalt ( Fig. 1d; Bryan and Moore, 1977;Rhodes et al, 1979;Pan and Batiza, 2003;Coogan, 2014). In many cases it can be shown that mixing occurred within weeks to months before eruption (e.g., Pan and Batiza, 2002;Costa et al, 2009;Moore et al, 2014).…”
Section: Observational Constraints On Morb Differentiationmentioning
confidence: 97%
“…Mush destabilization by replenishment can account for either of these. It can also account for the observation that MORB commonly contains diverse populations of phenocrysts and antecrysts, each recording a different petrogenetic history [74][75][76][78][79][80], as well as xenoliths of crystal mush [56,57]: when mush destabilizes and melts are transported upwards through it, they may pick up crystals and crystal clots from different parts of the system. Furthermore, even when crystals originate from a single location, the dynamics of mixing of melt and mush can be such that each crystal may take a different composition-time path, leading to the generation of multiple populations [64].…”
Section: (A) Melt Transportmentioning
confidence: 99%